2011
DOI: 10.1007/s12010-011-9173-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Parameters of L929 Cells Cultured on Plasma-Modified PDLLA Scaffolds

Abstract: Oxidative stress may produce high level of reactive oxygen species (ROS) following cell exposure to endogenous and exogenous factors. Recent experiments implicate oxidative stress as playing an essential role in cytotoxicity of many materials. The aim of this study was to measure intracellular malondialdehyde (MDA), advanced oxidation protein product (AOPP) levels, and superoxide dismutase (SOD) activities of L929 fibroblasts cultured on PDLLA, polyethylene glycol (PEG), or ethylenediamine (EDA) grafted PDLLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
(33 reference statements)
3
16
0
Order By: Relevance
“…The PEG‐modified TPU melt‐electrospun mat presented a higher cell viability compared to the unmodified counterparts at the end of 5 days ( p < 0.05). This underlined a study reported in the literature, in which PEG modification increased the cell adhesion, spreading, and proliferation . Additionally, the response of the nAg‐loaded PEG‐modified TPU mat was investigated in terms of its silver cytotoxicity.…”
Section: Resultssupporting
confidence: 70%
“…The PEG‐modified TPU melt‐electrospun mat presented a higher cell viability compared to the unmodified counterparts at the end of 5 days ( p < 0.05). This underlined a study reported in the literature, in which PEG modification increased the cell adhesion, spreading, and proliferation . Additionally, the response of the nAg‐loaded PEG‐modified TPU mat was investigated in terms of its silver cytotoxicity.…”
Section: Resultssupporting
confidence: 70%
“…The OD570 (sample) represents the measurement from the wells treated with nonmodified, EDA‐ or PEG‐modified scaffolds extract mediums, and the OD 570(control) represents the measurements from the wells treated cell culture medium only 19…”
Section: Methodsmentioning
confidence: 99%
“…The equilibrium between the ambient levels of the superoxide anion and cellular antioxidant capacity provided by SOD activity was broken at 72hpi. SOD are the free radical scavenger which can remove body's free radical, it have anti-oxidative stress function to maintaining body's in a healthy balance between oxidants and antioxidants (Han et al, 2014) MDA is a biomarker of lipid per-oxidation and its content represent the level of body's oxidative stress (Demirbilek et al, 2011). Therefore, determination of MDA and SOD can reflect the capability of elimination of free radicals in the body and the extent of CK cells injury during IBV infection (Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%